The Impact of Brain Metastases and Associated Neurocognitive Aspects on Health Utility Scores in EGFR Mutated and ALK Rearranged NSCLC: A Real World Evidence Analysis. (5th April 2019) - O'Kane, Grainne M.; Su, Jie; Tse, Brandon C.; Tam, Vivian; Tse, Tiffany; Lu, Lin; Borean, Michael; Tam, Emily; Labbé, Catherine; Naik, Hiten; Mittmann, Nicole; Doherty, Mark K.; et al.
Abstract: Background: In lung cancer, brain metastases (BM) and their treatment are associated with high economic burden and inferior health‐related quality of life. In the era of targeted therapy, real world evidence through health utility scores (HUS) is critical for economic analyses. Materials and Methods: In a prospective observational cohort study (2014–2016), outpatients with stage IV lung cancer completed demographic and EQ‐5D‐3L surveys (to derive HUS). Health states and clinicopathologic variables were obtained from chart abstraction. Patients were categorized by the presence or absence of BM; regression analyses identified factors that were associated with HUS. A subset of patients prospectively completed neurocognitive function (NCF) tests and/or the FACT‐brain (FACT‐Br) questionnaire, which were then correlated with HUS (Spearman coefficients; regression analyses). Results: Of 519 patients with 1, 686 EQ‐5D‐3L‐derived HUS, 94 (18%) completed NCF tests and 107 (21%) completed FACT‐Br; 301 (58%) never developed BM, 24 (5%) developed first BM during study period, and 194 (37%) had BM at study entry. The sample was enriched (46%) for EGFR mutations ( EGFR m) and ALK ‐rearrangements ( ALK r). There were no HUS differences by BM status overall and in subsets by demographics. In multivariable analyses, superior HUS was associated with having EGFR m/ ALK r ( p < .0001), no prior radiation for extracranial disease ( p < .001), and both intracranial ( p = .002) and extracranial disease control ( p < .01). HUS correlated with multiple elements of the FACT‐Br and tests of NCF. Conclusion: Having BM in lung cancer is not associated with inferior HUS in a population enriched for EGFR m and ALK r. Patients exhibiting disease control and those with oncogene‐addicted tumors have superior HUS. Abstract : With improved outcomes, more lung cancer patients are being diagnosed with brain metastases. This article evaluates the correlations between brain metastasis and health utility scores in lung cancer patients.